Identities of the incumbent and the successor in the family business succession: Review and prospects - Weining Li; Yunqiao Wang; Liebing Cao (Frontiers in Psychology, 2023)
IntroductionThe cognition and motivation of family business incumbents and the successors will directly influence succession behavior, yet they face identity challenges during succession due to the intersection of family and firm context, and their ability to overcome identity challenges will determine the success of the succession. However, as studies on their identity are fragmented and lack systematicity, there is a need to assess the relevant literature.MethodsDrawing from social identity theory (SIT) and role identity theory (RIT), this article adopts a systematic literature review approach to analyze 99 SSCI-indexed articles to explore family business succession from an identity perspective.ResultsThe article finds that the focus on the self-concept of the incumbent and the successor shifts from group identification to role identity perception and multi-roles, and succession behaviors are based on identity perception.DiscussionThis article summarizes a knowledge framework of the antecedents, connotations, and behavioral consequences of identity perception, revealing that family business succession from an identity perspective exhibits psychological and multidisciplinary characteristics, highlighting iterative and mutual features. Based on identity theories and succession research, this article proposes future directions from the research topics, research methods, and theoretical perspectives within the existing knowledge framework, such as cross-cultural and diachronic analysis, as well as from the theoretical perspectives of family, personality development, and pedagogy.